A Nontoxic Concentration of Cisplatin Induces Autophagy in Cervical Cancer. Issue 3 (March 2015) - Leisching, Gina; Loos, Benjamin; Botha, Matthys; Engelbrecht, Anna-Mart
<x xml:space="preserve">Abstract</x> Background Increasing resistance to cisplatin as well as the severity of the adverse effects limit the use of this drug, particularly at high doses. Evidence has implicated the importance of autophagy in cancer resistance as well as the fact that various chemotherapy agents induce autophagy in cancer cells. We therefore aimed to first assess the role of autophagy in cisplatin treatment and second to assess whether a nontoxic concentration of cisplatin, together with autophagy inhibition, is able to maintain its cancer-specific cytotoxic action. Methods Three human cervical cell lines were used: a noncancerous ectocervical epithelial cell line (Ect1/E6E7) and 2 cancerous cervical cell lines (HeLa and CaSki). Autophagy was monitored through the presence of the classical protein markers LC-3 II and p62 under basal and treatment conditions, and inhibited using bafilomycin and autophagy protein 5 (ATG5) siRNA under treatment conditions. Cell death was analyzed through examination of the apoptotic markers PARP and caspase-3 through Western blotting, as well as the Caspase-Glo assay to confirm caspase-3/7 activity. Cervical biopsies were analyzed for the presence of LC-3 using Western blotting and immunofluorescence to determine if a correlation between autophagic levels and the progression of the disease exists. Results Cervical cancer cells exhibit increased basal autophagic levels in comparison to the noncancerous counterparts. Cisplatin treatment enhanced autophagic activity in all 3 cell lines. Inhibition of this autophagic response together with cisplatin treatment leads to significant increases in cancer cell death. Expression profiles of LC-3 in normal, premalignant (low-grade and high-grade squamous intraepithelial lesion), and cancerous cervical tissue revealed that autophagy is significantly up-regulated in HSILs and carcinoma cervical tissue, which emphasized the role of autophagy in the progression of the disease. Conclusions The inhibition of autophagy improves the cytotoxicity of a nontoxic concentration of cisplatin and provides a promising new avenue for the future treatment of cervical cancer.